2016
DOI: 10.1002/admi.201500470
|View full text |Cite
|
Sign up to set email alerts
|

Local Probing of Ferroelectric and Ferroelastic Switching through Stress‐Mediated Piezoelectric Spectroscopy

Abstract: Strain effects have a significant role in mediating classic ferroelectric behavior such as polarization switching and domain wall dynamics. These effects are of critical relevance if the ferroelectric order parameter is coupled to strain and is therefore, also ferroelastic. Here, switching spectroscopy piezoresponse force microscopy (SS‐PFM) is combined with control of applied tip pressure to exert direct control over the ferroelastic and ferroelectric switching events, a modality otherwise unattainable in tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 52 publications
2
19
0
Order By: Relevance
“…In the piezo-response mode, a high frequency AC voltage superimposed at on a time variant DC bias voltage is applied to the conductive tip, causes the oscillation of electric dipoles in ferroelectric domains. They oscillate with the same frequency as the applied voltage 17 . The PFM tip as first-harmonic´s resonant contact signal through the tip-sample interaction can detect the amplitude and phase of this oscillation.…”
Section: Introductionmentioning
confidence: 98%
“…In the piezo-response mode, a high frequency AC voltage superimposed at on a time variant DC bias voltage is applied to the conductive tip, causes the oscillation of electric dipoles in ferroelectric domains. They oscillate with the same frequency as the applied voltage 17 . The PFM tip as first-harmonic´s resonant contact signal through the tip-sample interaction can detect the amplitude and phase of this oscillation.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have demonstrated phase transitions in BFO and PZT through application of nanoscale stress via an AFM tip due to alteration of the energies associated with stabilizing the different phases. Therefore, a systematic nanoindentation characterization of the BFO films was performed to reveal the impact of nanoscale stress on the evolution of the microstructure.…”
Section: Resultsmentioning
confidence: 99%
“…Detailed studies of the effects of electric field on mixed phase BFO have previously been performed using scanning probe microscopy, revealing both R → T and T → R phase transitions . The advent of band excitation piezoresponse force spectroscopy (BEPS) has enabled the collection of nanoscale piezoelectric hysteresis loops and detailed study of the accompanying phase transitions . While electric field is relatively simple to exert on the nanoscale via an atomic force microscope (AFM) tip, it has been challenging to achieve controlled stress‐induced phase transitions in a typical AFM setup.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations